Analisis Standarisasi Klasifikasi Armada Kapal pada PT. Samugara Artajaya - Syafril Zulmaidi; Jones Zenas Rante (Sekolah Tinggi Manajemen Transportasi (STMT Malahayati Jakarta), 2024)
The purpose of this study is to analyze and compare the two fleet inspections at PT. Samugara Artajaya. Ship Maintenance Management in a broad sense, is the actions of Managers (sea officers), which include all kinds of activities aimed at keeping the ship in a seaworthy condition (Sea Worthyness), meeting all requirements of the International Maritime Organization (IMO). Seaworthiness or operational worthiness is the condition of a ship that meets the requirements for ship safety, prevention of water pollution, manning, loading lines, loading, ship welfare and passenger health, legal status of the ship, ship safety management to sail in certain waters. All ships around the world are required to use ship inspection and monitoring services by the International or National Classification Agency, because this concerns the interests of ship insurance, ship owners, charterers, and the safety of the ship itself. Indicator variables, hull inspection includes all plates above the air, weather deck plates, sills and hatch equipment above the open deck and inside the open superstructure or open deckhouse and (side ports, cargo ports, front, side and rear ramps and front visors and side windows below the freeboard deck or closed superstructure deck etc., while the engine inspection variable indicators include the main propulsion engine, power transmission engine, shaft system, propulsion engine other than the main propulsion engine, boiler, hot oil heater, waste burner, pressure vessel, machining. The population in this study was the entire fleet of PT. Samugara Artajaya ships totaling eight (8) ships. The data analysis method used in this study is the non-parametric method of simple sign test and signed rank test or better known as the Wilcoxon signed rank test. The results of the analysis, so far the inspections carried out by the company have been as good as possible to achieve the classification standardization that has been carried out in the last 2 years and the comparative inspections carried out by the Classification Agency showed that there were differences where the inspections carried out by the company were smaller than the inspections carried out by the Indonesian Classification. The conclusion of this study, That on average the hull and engine inspections carried out by PT. Samugara Artajaya has not reached the maximum desired by the Indonesian Classification Standard.